The Development of The Booklet Educational Health Reproduction for High School Students - Yelviana Yelviana; Elsa Yuniarti; Sa'diatul Fuadiyah; Rahmawati Darussyamsu (Universitas Negeri Padang, 2020)
Adolescent period is transition from children to adult signed ny phisic alteration, mental and social life. In senior high school is the last adolescent peroid where is in thiss tmie they want to know many things, love chalenges and courageous of the risk. If they take any decision without smart consideration so will happen divergence of phisic, mental, and social life. For example is free sex before mariage. This case happen because the adolecents done get maximal information about keep their reproduction healthy. To fix this problem we can develope a booklet as aa simple media. This reserch purpose to result a education booklet about validation and practical the adolecent reproduction healty. This research is developing of researchusing there step from developing model 4-D. This reserch would held in the eleven grade SMAN 1 Batang Anai with 30 students as a subject of the research. Data collection instrument use validation questionnaire and practically. Based on the research have done, got validation precentage is 89,95% with validity criteria. While practically precentage is 89,42% with practical criteria. Thrus, the conclucion that have been resulted a validity and practical education booklet about adolecent reproduction healthy for senior high school student.